Digital Comic Media for Reading Comprehension of Fifth-Grade Students - Miqdad, Muhammad Zidna; Cahyaningtyas, Andarini Permata; Masnan, Abdul Halim (Yayasan Keluarga Guru Mandiri, 2026)
This study was motivated by the lack of media use in learning activities, causing students to have difficulty in reading comprehension of stories. This study aims to describe the development process, feasibility, and effectiveness of digital comic media. This research is a Research and Development of the ADDIE model with a quantitative approach. Data sources came from teachers, students, documents, and experts. Data collection is conducted through various test techniques, including pre-tests and post-tests, as well as non-test methods such as interviews, questionnaires, and documentation. Data were validated using item analysis. The data analysis technique consists of a normality test and a paired t-test. The results of material expert validation achieved a percentage of 93%, media expert validation achieved a percentage of 90%, student response questionnaires achieved percentages of 86% and 89%, and teacher response questionnaires achieved percentages of 88% and 92%. The results of the paired t-test indicate that the development of digital comics has significantly improved the story comprehension of fifth-grade students at SDN Podorejo 03. The development of digital comic media supports SDG 4 (Quality Education).